Accurate cover crack modelling of reinforced concrete structures subjected to non-uniform corrosion. Issue 12 (2nd December 2018) - Xi, Xun; Yang, Shangtong; Li, Chun-Qing
Abstract: Concrete cover cracking caused by reinforcement corrosion is a significant durability problem of reinforced concrete (RC) structures. Extensive research has been carried out in the last few decades while most were focused on corrosion of a single reinforcing bar. Very little research has examined the whole cover cracking of RC structures due to multiple reinforcement corrosion. This article develops a numerical model to predict the structural failure of the whole cover of concrete induced by corrosion of multiple reinforcing bars. Moreover, a non-uniform corrosion model is established based on experimental results, in contrast to conventional uniform assumption. Two typical cover failure modes under the non-uniform corrosion of multiple reinforcing bars are identified and discussed. The effects of cover thickness, reinforcement spacing, fracture energy of concrete, etc., on cover cracking patterns and crack width are also investigated. The derived numerical model is verified by comparing the results with those from experiments in literature. Accurate prediction of concrete cover cracking can allow timely maintenance of existing structures and rational design for new buildings which prolongs the service life of the RC structures.